“Senderización y Señalética de una Ciclo Ruta Turística que integra las Parroquias El Airo y Santa Teresita del Cantón Espíndola de la Provincia de Loja - Alama Gutierrez, Hugo Ruben (2017)
Tourism has become one of the main economic sources of Ecuador as it contributes to development by generating employment and foreign exchange. The province of Loja, its cantons and parishes are important tourist destinations in the south of the country because of their natural and cultural attractions. In places like the Parroquias El Airo and Santa Teresita del Cantón Espíndola has a great tourist potential, that is why it is necessary the tourist signage to satisfy the expectations of the visitors, providing a clear orientation of the existing tourist attractions. The present investigation denominated Senderización and Señalética of a cycle tourist route that integrates the parroquias El Airo and Santa Teresita of the Canton Espíndola of the province of Loja, aims to provide security and information thus achieving a greater influx of tourists and in this way contribute to the development Tourist site. The research work whose general objective consisted in: Elaborating the proposal of the Senderización and Señalética of a cycle touristic route that integrates the parishes El Airo and Santa Teresita of the Espirndola canton of the province of Loja, aims to contribute to the development of tourism in The localities and consists of three specific objectives: In the first objective the Tourist Diagnosis of the current situation of the tourist route cycle that integrates the parishes El Airo and Santa Teresita of the Espirndola canton of the province of Loja was proposed. The scientific, analytical, deductive and synthetic methods Allowed the internal and external analysis of the environment. In addition, Carla Ricaurte's matrix for the Tourist Diagnosis was applied, taking into account parish diagnoses and information issued by local GADs. Through the technique of direct observation and the records of the Ministry of Tourism, an inventory of tourism attractions was carried out to evaluate its current status and level of hierarchy. Interviews were conducted with the President of the GAD El Airo, President of an agricultural association and a local guide. The analysis of the SWOT matrix was concluded to define the strengths, opportunities, weaknesses and threats of the area. Regarding the second objective, it was proposed: To develop the proposal of Senderization and Signaltics of the cycle touristic route that integrates the parishes El Airo and Santa Teresita of the canton Espindola of the province of Loja. Inductive, scientific and direct observation techniques were applied, the study area was visited and the geo-referencing and planimetric survey of the path and the points for the proposed approach were performed using the global positioning system (GPS). Tourist signage in the cycle route, the technical specifications of the trail were determined taking as reference the rules of MINTUR. We used the Tourism Signature Corporate Manual of the Ministry of Tourism that standardizes the signage in Ecuador, to elaborate the corresponding signage of the route cycle.Regarding the third objective, which consisted of: To elaborate an environmental impact study of the possible damages caused by the Senderization and Signaltics proposal of a tourist route cycle. The analytical method, direct observation, qualitative matrix and quantitative identification of impacts of the author Leopold were used to identify and analyze the possible positive and negative impacts of the project proposal. Among the conclusions could be determined that the tourist route cycle has unique tourist potential to be exploited, so that through this research is intended to encourage the provincial and local authorities in terms of tourism so that at the time of being executed can be offered to Visitors a different option to know the different tourist attractions of the area. Also it is recommended to the Provincial Government of Loja the implementation of the proposal to be senderización and signage in the cycle route and to the local and cantonal authorities to give greater interest in the tourist field since it is an opportunity of development that is not being taken advantage of.